C-reactive protein as a mediator in the link between cardiometabolic index and osteoarthritis: insights from NHANES 2001–2010 - Yike Wang; Zeyu Liu; Haoyu Wu; Chunsheng Wang (Lipids in Health and Disease)
Abstract Background Evidence has noted associations of osteoarthritis (OA) with obesity and C-reactive protein (CRP). However, little is clarified about the link between cardiometabolic index (CMI) and OA and the mediating role of CRP. Methods Participants from NHANES 2001–2010 were enrolled. CMI was computed based on anthropometric and biochemical indexes, covering height, waist circumference, triglyceride, and high-density lipoprotein cholesterol. OA diagnosis data were derived from the Medical Conditions questionnaires. Multivariate logistic regressions, restricted cubic spline (RCS) analysis, subgroup analyses, and interaction tests were implemented to investigate the association. A mediation analysis was employed to verify the mediating role of CRP. Results After controlling for all covariates, CMI was significantly linked with OA (OR: 1.07, 95% CI (1.01, 1.13), P = 0.038). RCS analyses elicited a non-linear link between CMI and OA (P − non − linear = 0.0012). The inflection point was 0.54. Threshold effect analysis was conducted through two-segment linear regression, including the left side ( < = 0.54) (OR: 2.06, 95% CI: 1.03, 6.58) and the right side of the inflection point (> 0.54) (OR: 0.40, 95% CI: 0.15, 1.03). CRP partially mediated the link between CMI and OA, around 7.59% of the total effect. Conclusion CMI is positively linked with OA, with CRP mediating the link. This paper unveils novel perspectives on the mechanism that links CMI to OA. Managing CMI and monitoring CRP levels may alleviate OA.